The effect of different lighting times on survival and growth rate of gurami seeds (Oshpronemus gouramy) - Hidayat, Muhammad; Putriningtias, Andika; Rosmaiti, Rosmaiti (Universitas Malikussaleh, 2024)
This study aims to determine the effectiveness of different photoperiods on maturity and the effect of different light durations on survival and growth of gourami (Ospronemus gouramy) fry. The study was conducted on August 22th - September 22th in the Green House Samudra University.Test fish used is seed of gouramy measuring 5-6 cm. The methods used in this study was Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatments in this study were P1 (4 hours light, 20 hours dark), P2 (8 hours light, 16 hours dark), P3 (12 jam hours light, 12 hours dark), and P4 (16 hours light, 18 hours dark). Seeds of fish was put in a containing 20 liters of water volume with a stocking density of 10 tails each container. The frequency of feeding is done 4 times a day at 06.00 am, 12.00 am, 18 pm and 24.00 pm. The results showed that different natural feeding teratments had a significant effect on the absolute weight, absolute length growth, daily growth rate, survival, FCR, and water quality. The best treatment in this study was P1 treatment (4 hours light, 20 hours dark) because it had a high value compared to other treatments.Keywords: Gouramy; Growth; Photoperiod; Survival; Weight